Highly Dispersible and Bioavailable Curcumin but not Native Curcumin Induces Brown‐Like Adipocyte Formation in Mice. Issue 5 (5th February 2018) - Nishikawa, Sho; Kamiya, Misa; Aoyama, Hiroki; Nomura, Mami; Hyodo, Takuma; Ozeki, Aoi; Lee, Hyunjin; Takahashi, Tsukasa; Imaizumi, Atsushi; Tsuda, Takanori
Abstract : Scope: The induction of brown‐like adipocytes in white adipose tissue (WAT) is a potential therapeutic target for the treatment of obesity and metabolic disorders via the ability of these cells to release excess energy as heat in association with uncoupling protein 1. Some experimental trials suggest that curcumin (a yellow pigment from turmeric) has a suppressive effect on the accumulation of body fat. However, there is little evidence to show that curcumin induces the formation of brown‐like adipocytes and the molecular mechanisms involved remain elusive. In addition, in most experimental trials, high doses of curcumin are administered. Methods and results: Highly dispersible and bioavailable curcumin (HC, i.e., 4.5 mg native curcumin kg –1 ) but not the same dose of native curcumin induces the formation of brown‐like adipocytes in mouse inguinal WAT. Moreover, the formation of brown‐like adipocytes induced by HC in inguinal WAT may be mediated by the production of local norepinephrine from accumulated alternatively activated macrophages. Conclusion: These novel findings suggest that curcumin increases energy expenditure by inducing the formation of brown‐like adipocytes via a unique molecular mechanism. Importantly, they show that HC has significant bioactive effects in vivo at lower doses of curcumin. Abstract : The induction of brown‐like adipocytes in white adipose tissue (WAT) is a potential therapeutic target for the treatment of obesity and metabolic disorders. In the present study, it is demonstrated that highly dispersible and bioavailable curcumin but not the same dose of native curcumin induces the formation of brown‐like adipocytes in mouse inguinal WAT. Moreover, this effect may be mediated by the production of local norepinephrine following the accumulation of alternatively activated macrophages in iWAT.